Dietary strategies to promote glycogen synthesis after exercise - Ivy, J. L. (Canadian Journal of Applied Physiology, 2001)
Muscle glycogen is an essential fuel for prolonged intense exercise, and therefore it is important that the glycogen stores be copious for competition and strenuous training regimens. While early research focused on means of increasing the muscle glycogen stores in preparation for competition and its day-to-day replenishment, recent research has focused on the most effective means of promoting its replenishment during the early hours of recovery. It has been observed that muscle glycogen synthesis is twice as rapid if carbohydrate is consumed immediately after exercise as opposed to waiting several hours, and that a rapid rate of synthesis can be maintained if carbohydrate is consumed on a regular basis. For example, supplementing at 30-min intervals at a rate of 1.2 to 1.5 g CHO kg 1 body wt h 1 appears to maximize synthesis for a period of 4- to 5-h post exercise. If a lighter carbohydrate supplement is desired, however, glycogen synthesis can be enhanced with the addition of protein and certain amino acids. Furthermore, the combination of carbohydrate and protein has the added benefit of stimulating amino acid transport, protein synthesis and muscle tissue repair. Research suggests that aerobic performance following recovery is related to the degree of muscle glycogen replenishment.